Gas-phase kinetic of boron carbide chemical vapor deposition using BCl3+CH4+H2 mixture - Gupta A.; Nigam S.; Shinde V.M. (My University, 2025)
A detailed chemical kinetic mechanism consisting of 472 reactions and 61 species for the gas-phase thermal decomposition of BCl3+CH4+H2 mixtures is used to model the chemical vapor deposition (CVD) of boron carbide. The mechanism is constructed using a reaction mechanism generator (RMG), which is automatic and requires no or less human intervention. New functionality, considerable thermodynamic and kinetic data have been added to RMG to account for boron chemistry. The model considers all necessary reactions in the reaction pathways and reasonably predicts the experimental data available from the literature. The sensitivity analysis identifies crucial species responsible for boron carbide formation. Besides, a reduced mechanism (15 species and 26 reactions) is derived from a detailed mechanism, which could be used to expedite an effective CVD reactor design through numerical simulations. The performance of the reduced model is also evaluated concerning the complete mechanism, which shows that the reduced model can predict the reactor behavior reasonably well. © 2022 The American Ceramic Society.